Dampak Edmodo berbantuan Laboratorium Virtual terhadap Motivasi dan Kemandirian Belajar Siswa - A. Halim; Yusrizal Yusrizal; Elisa Elisa; Fitria Herliana; Dhieta Dewi Utami (Postgraduate, University of Mataram, 2022)
One of the difficulties that arise during online learning is the lack of motivation and independence in student learning. Teachers are required to be able to master various kinds of technology in order to be able to apply online learning which can increase motivation and independence. Edmodo is a learning medium that can be used during online learning and provides features that make communication and collaboration between teachers and students easier. The purpose of this study was to determine the impact of the application of Edmodo assisted by a virtual laboratory on students' learning motivation and independence. The design used in this study was a pretest-posttest control group design. The research sample was 60 X MIA students at SMAN 2 Peusangan. The experimental class uses Edmodo assisted by a virtual laboratory combined with PhET simulations, while the control class uses WhatsApp media. The data collection instrument uses a questionnaire on student learning motivation and independence that has been validated by experts. The results of the t-test analysis of learning motivation in the post-test experimental class and control class showed that there were significant differences. While the results of the t-test analysis of learning independence in the post-test experimental class and control class showed that there were also significant differences. The conclusion from the results of this study is that the application of Edmodo assisted by a virtual laboratory has a significant influence on learning motivation and independence, so it is effectively used in learning physics, especially in Newton's Law material.